2009
DOI: 10.1007/s10533-009-9287-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid organic matter mineralization coupled to iron cycling in intertidal mud flats of the Han River estuary, Yellow Sea

Abstract: Organic matter oxidation represents a transfer of elements to inorganic nutrients that support biological productivity and food web processes. Therefore, quantiWcation of the controls of organic matter mineralization is crucial to understanding the carbon cycle and biogeochemical dynamics in coastal marine environments. We investigated the rates and pathways of anaerobic carbon (C) oxidation in an unvegetated mud Xat (UMF) and a vegetated mud Xat (VMF) of the Ganghwa intertidal zone of the macro-tidal Han Rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 76 publications
3
33
0
3
Order By: Relevance
“…Our results also suggest that the presence of plants increases the competitiveness of FeR% and lowers SR%, which is in accordance with that found in other studies, including mangrove mesocosms in North Queensland, Australia (Kristensen & Alongi 2006), tidal marshes on Sapelo Island, USA (Kostka et al 2002a) and Skidaway Island, USA (Hyun et al 2007), Han River estuary, Korea (Hyun et al 2009), Patuxent River, USA (Neubauer et al 2005), and mangrove forests on Phuket Island, Thailand (Kristensen et al 2000).…”
Section: Total Anaerobic Metabolismsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also suggest that the presence of plants increases the competitiveness of FeR% and lowers SR%, which is in accordance with that found in other studies, including mangrove mesocosms in North Queensland, Australia (Kristensen & Alongi 2006), tidal marshes on Sapelo Island, USA (Kostka et al 2002a) and Skidaway Island, USA (Hyun et al 2007), Han River estuary, Korea (Hyun et al 2009), Patuxent River, USA (Neubauer et al 2005), and mangrove forests on Phuket Island, Thailand (Kristensen et al 2000).…”
Section: Total Anaerobic Metabolismsupporting
confidence: 93%
“…The unexplained proportion may have been caused by underestimated SR% in both types of mesocosm, but particularly for the vegetated mesocosms due to rapid sulfide reoxidation (Luo et al 2016). The unexplained proportion might also have been caused by CO 2 formation via fermentation (Jørgensen 2000, Hyun et al 2009 or by other terminal electronaccepting processes, such as denitrification and manganese (Mn) reduction. However, the contributions of NO 3 − and Mn(IV) to organic C mineralization may have been small, because their concentrations are much lower than concentrations of SO 4 2− and Fe(III) in sediments of the Min River estuary tidal marsh (Luo et al 2014).…”
Section: Total Anaerobic Metabolismmentioning
confidence: 99%
“…Microbial Fe reduction has been quantified directly in sediments of various coastal oceans (Gribsholt et al, 2003;Kostka et al, 2002a, b;Hyun et al, 2007Hyun et al, , 2009b and indirectly in deeper continental margins (Thamdrup and Canfield, 1996;Jensen et al, 2003;Kostka et al, 1999). Earlier estimation from 16 different continental margin sediments indicated that Fe(III) reduction contributed 22 % on average to anaerobic carbon oxidation .…”
Section: Org Oxidation Dominated By Manganese Reduction In the Ubmentioning
confidence: 99%
“…However, in sediments where manganese and iron oxides are abundant or rapidly recycled, microbial reduction of manganese and iron can be the dominant electron-accepting processes over sulfate reduction (Sørensen and Jørgensen, 1987;Aller, 1990;Canfield et al, 1993b). The significance of dissimilatory iron reduction for C org oxidation is well established in the sediments of various continental margins and coastal wetlands Thamdrup and Canfield, 1996;Jensen et al, 2003;Kostka et al, 2002a, b;Vandieken et al, 2006;Hyun et al, 2007Hyun et al, , 2009b. However, only a few locations such as the Panama Basin (Aller, 1990), the coastal Norwegian trough in Skagerrak and an adjacent fjord (Canfield et al, 1993a, b;Vandieken et al, 2014), the Black Sea shelf , and the continental shelf of the northern Barents Sea (Vandieken et al, 2006;Nickel et al, 2008) are known where microbial manganese reduction significantly contributes to carbon mineralization.…”
mentioning
confidence: 99%
“…Due to the high sulfate concentration (28 mM) in seawater, sulfate reduction is considered to be among the most important anaerobic C org mineralization pathways in marine sediments (Blackburn et al 1994;Holmer and Nielsen 1997;Holmer et al 2001;Hyun et al 2007Hyun et al , 2009). …”
Section: Introductionmentioning
confidence: 99%